2018
DOI: 10.33607/bjshs.v1i88.151
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Difficulties at Work of Physical Education Teachers

Abstract: Research background and hypothesis. In recent years, the phenomenon of stress and burnout among physical education  teachers  has  been  evidenced  by  researchers  from  many  countries.  It  should  be  noted  that  all  those studies about work difficulties of physical education teachers are individual. However, despite a large number of studies conducted and the progress made in this area, a universally accepted survey identifying five most important difficulties in physical education teachers’ work usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…For example, physical education is conventionally considered too boring, which sometimes it makes obstacles for elementary school students. In research conducted by [26] confirmed that difficulties in physical education so far include: low physical activity status, limited equipment, lack of time, number of students, loss of motivation and excessive daily workload. [27] emphasized that students with low skills are usually less confident and often unprepared to learn.…”
Section: Discussionmentioning
confidence: 97%
“…For example, physical education is conventionally considered too boring, which sometimes it makes obstacles for elementary school students. In research conducted by [26] confirmed that difficulties in physical education so far include: low physical activity status, limited equipment, lack of time, number of students, loss of motivation and excessive daily workload. [27] emphasized that students with low skills are usually less confident and often unprepared to learn.…”
Section: Discussionmentioning
confidence: 97%
“…This kind of condition must be designed so that students are interested in moving and can develop their manipulative motion skills. Strengthened on the research conducted by Trinkūnienė & Kardelienė (2013), asserts that difficulties in learning to move during this time include: low physical activity status, limited equipment, lack of time, number of students, loss of motivation and excess daily workload. Robinson (2011), asserts students who have low skills usually lack confidence and are often unprepared to learn.…”
Section: Discussionmentioning
confidence: 99%
“…Šiuos rezultatus patvirtina ir kitų autorių tyrimai apie dabartinėje darbo rinkoje nustatytą profesinių kūno kultūros ugdytojų siekių mažėjimą, kuriam būdingas sumažėjęs pasitikėjimas ir savimi, ir savo kompetencija (Stočkus, 2014). Taip pat pastebėta, kad ugdytojai abejoja savo gebėjimais profesionalai dirbti bei nuvertina ne tik savo profesinius pasiekimus, bet ir savo pačių svarbą ugdymo institucijoje (Trinkūnienė ir Kardelienė, 2013). Tai dažniau būdinga žemos savigarbos ugdytojams, kurie mano, jog jų asmeninis indėlis į institucijos veiklą yra mažai reikšmingas (Thorburn, 2014).…”
Section: Tyrimo Rezultatų Aptarimasunclassified